The Fear Within: Gender Differences in Fear of Failure among Senior High School Students and Implications for Guidance and Counseling - Siti Nurhaliza; Henny Indreswari; Khairul Bariyyah; Adi Atmoko; IM Hambali (ProGCouns: Journal of Professionals in Guidance and Counseling, 2026)
Adolescents today are confronted with growing pressures in both academic and social spheres, which can trigger anxiety around the prospect of failing. Among high school students in particular, these pressures commonly take the form of achievement expectations, scholastic rivalry, and demands placed by parents and the broader community. These circumstances tend to generate mental and emotional strain, shaping how students interpret their successes and setbacks throughout their educational journey. The present preliminary investigation explored how fear of failure operates among senior high school students, centered on five key dimensions: concerns about public humiliation and shame, worries over a diminished sense of self-worth, apprehension regarding an uncertain future, fear of losing one is standing in social circles, and anxiety about letting down those who matter most to them. A quantitative descriptive design was used with 142 students selected through purposive sampling. The study used the Performance Failure Appraisal Inventory (PFAI), a 25-item, four-point Likert scale, to measure students' fear of failure. The measured fear-of-failure reliability was high (Cronbach's α = 0.899). Descriptive statistics (means, standard deviations, frequencies) were analyzed using SPSS. Results showed mean scores above the midpoint of the scale for all five dimensions, indicating a relatively high overall fear of failure. Fear of lowered self-esteem was most prevalent (M = 3.2254), followed by fear of loss of social influence (M = 3.1197), fear of future uncertainty (M = 3.0986), fear of disappointing significant others (M = 3.0704), and fear of humiliation and embarrassment (M = 3.0352). The majority of the students agreed or strongly agreed that academic pressure contributed to fear of lowered self-esteem, fear of future uncertainty, fear of loss of social influence, and fear of disappointing significant others.